Mastoid Dressing in Ear Surgery: Is it Still Relevant? - Rahul Naga; Tejpal Singh Bedi; Renu Rajguru; Inderdeep Singh; Saurabh Mahajan (Bengal Journal of Otolaryngology and Head Neck Surgery, 2021)
Introduction